Equality, Equity, Public Administration and School Inspectorate - Cuadrado Muñoz, Francisco J. (Avances en Supervisión Educativa, 2025)
Equality and equity continue to be inseparable and controversial concepts in democratic societies, and even continue to be the subject of interest and controversy in social networks and political debates, due to the interpretations they give rise to and the lack of consensus in their definition. In recent decades, public administration has become more sensitive to the need to efficiently apply these principles, which also affect the exercise of educational inspection and supervision. Therefore, it is necessary to adopt a coherent and proven European inspection model that allows for the evaluation and supervision of the equity and quality of educational centers and the improvement of the entire system.
Keywords: Equality, equity, public administration, school inspection